2010
DOI: 10.1002/adv.20192
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and property evaluation of nanocomposites based on polyurethane‐modified epoxy/montmorillonite systems

Abstract: Montmorillonite nanoclay and polyurethanes obtained from polyethylene glycol (PUR 400) and polyoxypropylene diol (PUR 1002) were used to enhance the mechanical properties of an epoxy resin. Maximum impact strength improvement was obtained with compositions containing 2% nanoclay and 10% PUR 400 as well as that with 1% nanoclay and 15% PUR 400, corresponding to 110% and 75%, respectively, in relation to the unmodified epoxy resin. Moreover, a 10-fold increase was observed with respect to the flexural strain at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 35 publications
3
26
0
1
Order By: Relevance
“…Moreover, there are many factors that may affect the T g results, such as curing temperature and time [75][76][77] , the modification of clay, the level of dispersion and the space between sheets [73] . The findings of this trend in T g results were found to be in close agreement to the work carried out by other researchers [8,73,[75][76][77][78][79] . Table 7 and Figure 14 summarize the results of thermal conductivity of neat vinyl ester and the corresponding nanocomposites.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 95%
See 1 more Smart Citation
“…Moreover, there are many factors that may affect the T g results, such as curing temperature and time [75][76][77] , the modification of clay, the level of dispersion and the space between sheets [73] . The findings of this trend in T g results were found to be in close agreement to the work carried out by other researchers [8,73,[75][76][77][78][79] . Table 7 and Figure 14 summarize the results of thermal conductivity of neat vinyl ester and the corresponding nanocomposites.…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 95%
“…Polymers with various particulate fillers have been successfully reinforced to enhance their stiffness and toughness, as well as improving their resistance to fire and ignition and also their barrier properties [6][7][8][9] . The incorporation of the particulate fillers often results in unwanted properties such as brittleness and opacity.…”
Section: Introductionmentioning
confidence: 99%
“…In conclusion, it is worth mentioning that many factors can be important in changing the T g value, for example, the curing temperature and time, the modification of the layered silicate, and the intercalation level between sheets. The T g results were found to be in close agreement with the work reported in other studies (Alateyah, Dhakal, & Zhang, 2014;Bakar, Kostrzewa, Hausnerova, & Sar, 2010;Yasmin, Luo, Abot, & Daniel, 2006).…”
Section: Differential Scanning Calorimetry (Dsc)supporting
confidence: 82%
“…This effect was observed in both immiscible thermoplastic systems [7][8][9] and epoxies with two phase structures formed by the reaction-induced phase separation (RIPS) [10] of a modifier dissolved in an uncured resin. The enhanced mechanical performance of epoxy systems was mostly observed in liquid rubbers and clays [11][12][13] and in combinations of thermoplastics (PEEK, PEI, PES, ABS) and clays [14][15][16][17][18][19][20]. The synergistic effect of the nanofiller consists in its complex effect on the multiphase system by reinforcement, leading also to a change in the component parameter profile combined with a significant influence on the structure and parameters of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…The primary shortcoming is the increase in viscosity that limits the content of the modifier. An increasing number of studies have indicated not only that nanofillers (NF) can compensate for the stiffness reduction of impact-modified polymeric systems but also that a suitable combination of NF and a polymeric modifier can also provide a synergistic effect (e.g., further increasing the material toughness) [7][8][9][10][11][12][13][14][15][16]. The enhanced efficiency of impact modifiers allows their content to be reduced.…”
Section: Introductionmentioning
confidence: 99%